Marketing mix dynamism and performance: evidence from commercial firms - Martínez-Ruiz, M. P.; Dias, Á.; Blazquez-Resino, J. J. (Perspectiva Empresarial, 2014)
We focused on the analysis of marketing mix dynamic capabilities, taking into account their influence on customer, market and financial performance. In order to achieve this research goal, 201 SMEs in the Portuguese commercial sector were contacted and personally administered a questionnaire pertaining to the presence of diverse marketing mix dynamic capabilities. Data were analyzed by means of factorial analyses of the main components, as well as linear parametric regressions. Our findings show that there is a clear relationship between marketing mix dynamic capabilities and diverse performance metrics. Especially, the marketing dynamic capabilities related to aspects external to the product exert the greatest impact. This study highlights how Portuguese company managers are conscious of the importance of developing marketing mix dynamic capabilities and to adapt them to the changes in the environment.